Generating a three-dimensional non-fullerene electron acceptor by combining inexpensive spiro[fluorene-9, 9′-xanthene] and cyanopyridone functionalities. (6th April 2018) - Kadam, Gajanan; Anuradha,; Agarwal, Anubha; Puyad, Avinash; La, Duong Duc; Evans, Richard A.; Li, Jingliang; Gupta, Akhil; Bhosale, Sheshanath V.
Abstract : A spiro[fluorene-9, 9′-xanthene]-functionalized non-fullerene acceptor A1 [D : A1 = 1 : 1.2; P3HT(D) = 5.84%, PTB7(D) = 7.21%]. Abstract : Through the combination of cheaply synthesized structural fragments, spiro[fluorene-9, 9′-xanthene] – otherwise termed low-cost spiro – and cyanopyridone, herein we report a new, three-dimensional, small molecule non-fullerene electron acceptor, (5 Z, 5′ Z, 5′′ E, 5′′′ E )-5, 5′, 5′′, 5′′′-(((( S )-spiro[fluorene-9, 9′-xanthene]-2, 2′, 7, 7′-tetrayl)tetrakis(thiophene-5, 2-diyl))tetrakis(methaneylylidene))tetrakis(4-methyl-1-octyl-2, 6-dioxo-1, 2, 5, 6-tetrahydropyridine-3-carbonitrile) [A1 ], which was synthesized for use in solution-processable bulk-heterojunction devices and was fully characterized by proton and carbon NMR spectroscopies together with elemental analysis.A1 was synthesized by a facile synthetic methodology using a Knoevenagel condensation reaction and was found to be highly soluble in a variety of common processing solvents such as chloroform and o -dichlorobenzene. Owing to its envisioned design, A1 displayed promising optoelectronic properties, and energy levels complementing those of the conventional donor polymers poly(3-hexylthiophene) [P3HT] and poly(4, 8-bis[(2-ethylhexyl)oxy]benzo[1, 2- b :4, 5- b ′]dithiophene-2, 6-diyl3-fluoro-2-[(2-ethylhexyl)carbonyl]-thieno[3, 4- b ]thiophenediyl) [PTB7]. Given its energy levels, solubility and excellent film forming capability, A1 was used in bulk-heterojunction devices as an n-type semiconducting component. The device performances [D : A 1 : 1.2 = 5.84% (P3HT); 7.21% (PTB7)] validated the design and use ofA1 as an efficient non-fullerene acceptor.